2012
DOI: 10.4103/2230-8229.98302
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of self-medication with analgesics among Iranian University students in central Iran

Abstract: Background:Self-medication is defined as the use of drugs for the treatment of self-diagnosed disorders. It is influenced by factors such as education, family, society, law, availability of drugs and exposure to advertisements. This study was performed to evaluate self-medication with analgesics and its pattern among different groups of Iranian University Students.Materials and Methods:A randomized, cross-sectional, multicenter study was conducted from December 2009 to February 2010. The target population of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
80
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 19 publications
24
80
5
3
Order By: Relevance
“…However we found no significant association between being covered by health insurance and practicing self-medication, this was in line with study conducted by Sarahroodi et al (2012) who reported no statistically significant difference between self-medication and having or not having medical insurance [29]. On contrary, Widayati et al (2011) [26] found that Indonesian who had perceived access to health care (having insurance) were 1.47 times more likely to selfmedicate than those who reported no access to health care (OR = 1.47).…”
Section: Factors Associated With Self-medicationsupporting
confidence: 81%
“…However we found no significant association between being covered by health insurance and practicing self-medication, this was in line with study conducted by Sarahroodi et al (2012) who reported no statistically significant difference between self-medication and having or not having medical insurance [29]. On contrary, Widayati et al (2011) [26] found that Indonesian who had perceived access to health care (having insurance) were 1.47 times more likely to selfmedicate than those who reported no access to health care (OR = 1.47).…”
Section: Factors Associated With Self-medicationsupporting
confidence: 81%
“…This agrees with results from previous studies. [14,16] there is another study in Germany shown the opposite result. [17] Most of the analgesics user in this study are taking one tablet mostly for minor pains such as fever and headache which shows lack of information about appropriate adult dose which agrees with a Norwegian study which says that their respondents were using a lower dose of OTC drugs and had not exceeded the maximum dose.…”
Section: Discussionmentioning
confidence: 71%
“…[23,29] While the study in Iran that shows the most common source of information relied on by respondents was friends and family or advice from other people (54.7%). [16] Our study has strength and weakness. The strengths include the use of a large area of the general population; it is not limited to the specific cities or level of education like other studies.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 We found that paracetamol and NSAIDs with percentage of (23.3%) and (4.4%) respectively compared to other drug classes are the most common used medications in all medical years especially 4 th year medical students and this agrees with GCMS students, North West Ethiopia Egypt, Iranian college students in Qom city previous KAU study Western Nepal. 13,[15][16][17] Our results shows that antianxiety and opioids are the least used drugs and this could be linked to the knowledge of the risk of the side effects of these drugs, the cost, and the strict system in purchasing these kind of drugs.…”
Section: Discussionmentioning
confidence: 99%